2015
DOI: 10.1111/nmo.12666
|View full text |Cite
|
Sign up to set email alerts
|

Majority of symptoms in esophageal reflux PPI non‐responders are not related to reflux

Abstract: Background Genesis of persistent gastro-esophageal reflux symptoms despite proton pump inhibitor (PPI) therapy is not fully understood. We aimed at determining reflux patterns on 24-h pH-impedance monitoring performed on PPI and correlating impedance patterns and symptom occurrence in PPI non-responders. Methods 78 PPI non-responder patients underwent 24-h pH-impedance monitoring on PPI. Reflux impedance characterization included gastric and supragastric belches and proximal extent of reflux. Symptoms were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 21 publications
1
51
1
9
Order By: Relevance
“…The number of reflux events at on‐therapy impedance‐pH monitoring is directly related to AET at off‐therapy pH testing, but few studies have documented the clinical utility of this parameter in PPI‐refractory patients evaluated during ongoing therapy . Despite their well‐recognized limitations, symptom‐reflux association indexes are considered worthwhile for the clinical evaluation of patients with suspected reflux disease: however, their positivity is directly related to high reflux rates, only a minority of reflux events are associated with symptoms, and discordant positivity has been regarded as unreliable . In clinical practice, patients often do not perceive symptoms during a 24 hours study or admit inaccurate symptom recording, making a diagnosis based on positive symptom‐reflux association overly patient‐dependent.…”
Section: Discussionmentioning
confidence: 99%
“…The number of reflux events at on‐therapy impedance‐pH monitoring is directly related to AET at off‐therapy pH testing, but few studies have documented the clinical utility of this parameter in PPI‐refractory patients evaluated during ongoing therapy . Despite their well‐recognized limitations, symptom‐reflux association indexes are considered worthwhile for the clinical evaluation of patients with suspected reflux disease: however, their positivity is directly related to high reflux rates, only a minority of reflux events are associated with symptoms, and discordant positivity has been regarded as unreliable . In clinical practice, patients often do not perceive symptoms during a 24 hours study or admit inaccurate symptom recording, making a diagnosis based on positive symptom‐reflux association overly patient‐dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Laryngeal hypersensitivity may play a role in symptom recognition in laryngeal irritation, similar to the concept of esophageal hypersensitivity in patients with persistent troublesome GERD symptoms. 42, 43 At the same time, it is possible that patients enrolled in a clinical trial may be more likely to feel better with regards to health related outcomes, translating to improvements in psychosocial questionnaire results. While this chicken and egg phenomenon is unclear, our results do support the interplay between psychosocial factors and symptom generation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that patients with refractory gastroesophageal reflux symptoms often did not have GERD, [1,3,21] and that those patients diagnosed as GERD were more related with nonacid reflux (weakly acid and alkali reflux). [22–27] Consistent with the above studies, our findings showed 45.2% patients with refractory gastroesophageal reflux symptoms were associated with nonacid reflux and 16.1% patients were considered as FH.…”
Section: Discussionmentioning
confidence: 99%